2009
DOI: 10.3329/jhpn.v26i4.1890
|View full text |Cite
|
Sign up to set email alerts
|

Infant-feeding Practices among HIV-infected Mothers in an HIV-treatment Programme

Abstract: The transmission of HIV via breastmilk has led to various recommendations for HIV-infected mothers. In this study, the feeding practices of HIV-infected mothers in the first six months of their infants' lives were evaluated. In total, 103 consecutive mothers of children, aged 6-24 months, were evaluated for their feeding practices in the first six months of their infants' lives. The mothers were recruited in two cohorts based on their entry (PMTCT cohort) or non-entry (non-PMTCT cohort) to an HIV MTCT-preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 6 publications
2
11
1
Order By: Relevance
“…This is closely related to the transmission rates of 68.6% and 6.7% respectively obtained for those with no participation and those with full participation, reported by Okechukwu et al 8 in Gwagwalada Abuja. It is noteworthy that the overall rates of transmission quoted in the previous studies for those that were diagnosed early and had full participation in PMTCT 8,11 , are close to the overall rate of 6.4% obtained in this study. This, therefore clearly suggests a positive impact of the current intervention on PMTCT.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This is closely related to the transmission rates of 68.6% and 6.7% respectively obtained for those with no participation and those with full participation, reported by Okechukwu et al 8 in Gwagwalada Abuja. It is noteworthy that the overall rates of transmission quoted in the previous studies for those that were diagnosed early and had full participation in PMTCT 8,11 , are close to the overall rate of 6.4% obtained in this study. This, therefore clearly suggests a positive impact of the current intervention on PMTCT.…”
Section: Discussionsupporting
confidence: 86%
“…However, a higher rate of transmission of 70.4 % and 68.3 % respectively were reported in university of Benin Teaching Hospital 11 and Abuja 8 during the era of PMTCT programme. This was attributed to late detection of HIV in pregnancy and lack of full participation in the preventive interventions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, women of lower socio-economic status found it difficult to continue formula feeding when there was an interruption in the supply of free formula (Doherty et al, 2006 b). Similar results were reported from Kenya (Kiarie et al, 2004) and Nigeria (Sadoh et al, 2008). Besides the cost of formula, other socio-economic considerations including access to clean water and fuel for replacement food preparation, problems with replacement food preparation, electricity, and other infrastructure necessary for the safe and hygienic preparation of formula milk were reported by the mothers in this study.…”
Section: Challenges Of Exclusive Replacement Feedingsupporting
confidence: 88%
“…Quantitative data was presented in the form of tables and textual summaries. Results from this study showed poor knowledge of appropriate infant methods as only 46 (44.7%) mothers were satisfied with the infant feeding counseling they had received from the health personnel. Poor clinic attendance by 61 (59.2%) of the mothers may have led to short and few sessions and it also affected the time of infant feeding thus the poor quality of counseling.…”
mentioning
confidence: 78%